Prescribing Trends of Antihistamines in the Outpatient Setting in Al-Kharj - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: This study aims to illustrate the prescribing trends of antihistamines in the outpatient setting in Al-Kharj. Materials and Methods: This is a retrospective study that included the evaluation of antihistamines in the outpatient setting in a public hospital in Al-Kharj. The data were collected from the pharmacy-based computer system. Results: The total number of prescriptions that included antihistamines was 799. Most of the prescribed antihistamines were first-generation sedating antihistamines (chlorphenamine and diphenhydramine) (66.33%). About 63.20% of the prescribed antihistamines included chlorpheniramine followed by cetirizine (19.27%) and loratadine (14.39%). Conclusion: Antihistamines were prescribed commonly in the outpatient setting mainly first-generation sedating antihistamines. It is recommended to increase the awareness of healthcare providers about the efficacy and the side effects of antihistamines and to encourage them to use these agents wisely.